2015
DOI: 10.1080/15226514.2015.1130018
|View full text |Cite
|
Sign up to set email alerts
|

The efficient role of aquatic plant (water hyacinth) in treating domestic wastewater in continuous system

Abstract: In this study, water hyacinth (Eichhornia crassipes) was used to treat domestic wastewater. Ten organic and inorganic parameters were monitored in three weeks for water purification. The six chemical, biological and physical parameters included Dissolved Oxygen (DO), Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Ammoniacal Nitrogen (NH3-N), Total Suspended Solids (TSS), and pH were compared with the Interim National Water Quality Standards, Malaysia River classification (INWQS) and Water Qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
2
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 21 publications
6
53
2
7
Order By: Relevance
“…According to Rommens’ study (19), a remarkable difference existed in the present study, that is, pH value average increased by 0.11 after the MS-PFI treatment. Rezania et al (20) indicated that a tiny growth in pH that ranges from 6.95 to 7.1 during an Eichhornia crassipes purification system. Some researchers considered that a decline of pH may drive by acid secretion from plant roots, and degradation of organic matter by aerobic organisms (21).…”
Section: Discussionmentioning
confidence: 99%
“…According to Rommens’ study (19), a remarkable difference existed in the present study, that is, pH value average increased by 0.11 after the MS-PFI treatment. Rezania et al (20) indicated that a tiny growth in pH that ranges from 6.95 to 7.1 during an Eichhornia crassipes purification system. Some researchers considered that a decline of pH may drive by acid secretion from plant roots, and degradation of organic matter by aerobic organisms (21).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the removal efficiency for total dissolved solid was 67.72% in control whereas 69.97% for phytoremediation. About 11% reduction efficiency for TDS was observed by [10] while treating the domestic wastewater using Eichhornia crassipes. However, reduction of 26% for TDS was reported by [12] in Eichhornia crassipes.…”
Section: Resultsmentioning
confidence: 98%
“…As shown in Fig.1, a small increase was observed in pH range from 6.25 to 6.63 (6.08%) by phytoremediation whereas 17.44 % decrease of pH range was observed in control. Study by [10] found an increase of 13% pH value while treating the domestic wastewater using Eichhornia crassipes. Study by [11] observed that aeration reduces rate of pH reduction was higher in phytoremediation treatment with Eichhornia crassipes in comparison to treatment by Pistia stratiotes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under appropriate environmental conditions, WH may double its biomass through asexual reproduction within two weeks; ten WH plants can produce 655,360 new plants in eight months, and they can cover the water surface by about half a hectare [7]. The WH's excessive amount and its expansive growthresulted in to interfere with shipping, irrigation and electricity generation [8]. In Selorejo dam, Malang, East Java, Indonesia, 100 hectares of the total reservoir area of 650 hectares is covered by WH.…”
Section: Introductionmentioning
confidence: 99%